Optimizing usage of diatomaceous earth as nitric oxide delivery platform : introduction of layer-by-layer coating technique - Yendri, Sheilla (Nanyang Technological University, 2020)
Over the past decades, many researches have been done to design a delivery platform for nitric oxide (NO) that can release NO in a steady and long-lasting manner for the purpose of biomedical therapies such as promoting angiogenesis for wound healing. One proposed design is by using diatomaceous earth (DE) porous surface modification to accommodate the NO donors. However, additional adjustments are needed to optimize the usage of DE as an ideal NO delivery platform. In this report, the executed adjustments were varying the thiol group concentration and applying two coating methods in order to achieve the best NO loaded DE delivery vehicle performance in terms of NO loading capacity and NO release profile. The two coating methods used were alginate encapsulation and layer-by-layer (LBL) technique. Compared to the encapsulation method, layer-by-layer technique is shown to provide a much steadier NO release profile that can last for up to 2 weeks. In addition, the exposure of LBL coating also reduces the cytotoxicity of NO loaded DE for 24 hours. The performance results of these two methods were quantified by plotting their NO cumulative release profile and testing their cell viability.